2014
DOI: 10.3109/09553002.2014.954058
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of extremely low frequency electromagnetic fields exposure on Alzheimer's disease in rats

Abstract: The present study indicated that short-term exposure of 100 μT/50 Hz ELF-EMF had no effects on cognition and memory of rats, and did not alter the expression of Aβ and the neuron morphology. However, more comprehensive studies are still required to elucidate the possible effects and underlying mechanisms of ELF-EMF exposure on living organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Morris water maze was first reported in 1984 (Morris, 1984), and subsequently became one of the most frequently used laboratory tools in behavioral neuroscience. In previous study, our group had shown that 100 mT ELF-EMF exposure for 12 weeks did not affect the spatial learning in MWM (Zhang et al, 2015b). In the present study, similar results were observed even though the exposure time was prolonged to 24 weeks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Morris water maze was first reported in 1984 (Morris, 1984), and subsequently became one of the most frequently used laboratory tools in behavioral neuroscience. In previous study, our group had shown that 100 mT ELF-EMF exposure for 12 weeks did not affect the spatial learning in MWM (Zhang et al, 2015b). In the present study, similar results were observed even though the exposure time was prolonged to 24 weeks.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous work has shown that short term ELF-EMF exposure did not affect learning and memory as assessed by Morris water maze (Zhang et al, 2015b). In the present study, we employed adult male rats to investigate whether the exposure to ELF-EMF (50 Hz, 100 mT) would influence behavior, including anxiety-like behavior, depression-like behavior, spatial learning, fear learning and memory using more comprehensive measurements.…”
Section: Introductionmentioning
confidence: 93%
“…Sensitivities for IL-9, IL-10, and TNF-α assay were 0.53, 1.51, and 2.51 pg/ mL, respectively. 4,29 Statistical Analysis…”
Section: Cytokines Assaymentioning
confidence: 99%
“…1 Some studies have indicated that exposure to ELF-EMFs has possible health hazards such as cancer, leukemia, neurodegenerative diseases, and infertility. [2][3][4][5] Despite potential negative impacts of ELF-EMFs, nowadays, they can effectively be used to diagnose and treat various diseases such as cancer, muscle regeneration, diabetes, arthritis, and neurological disorders. 1,6 These disorders can be caused by abnormal immune response to harmful invaders.…”
mentioning
confidence: 99%
“…(1993) and London et al (1991), suggest that the relationship was not proven. Several studies (Kumar et al, 2013;Hancı et al, 2013;Hao et al, 2013;Zhang, Liu, Zhang, & Li, 2015) using experimental animals have also been conducted since the sixties and the results are still varied, ranging from no-effect images, no effect on behavioral changes until the occurrence of defects in the offspring. Although the results of examination of the effect of electromagnetic exposures on animal indicate the presence of adverse effects, such exposures effect does not prove harmful in residential, working environments and human health (World Health Organisation [WHO], 1987).…”
Section: Literature Reviewmentioning
confidence: 99%